Ethanol Inhibits Clearance of Brain Serotonin by a Serotonin Transporter-Independent Mechanism - Daws, Lynette C. (J Neurosci, 2006)
Brain serotonin (5-HT) modulates the neural and behavioral effects of ethanol in a manner that remains poorly understood. Here we show that treatment with physiologically relevant (i.e., moderately intoxicating) doses of ethanol inhibits clearance of 5-HT from extracellular fluid in the mouse hippocampus. This finding demonstrates, in vivo, a key molecular mechanism by which ethanol modulates serotonergic neurotransmission. The 5-HT transporter (5-HTT) is the principle means of 5-HT reuptake in the brain and an obvious candidate mechanism for the effect of ethanol to inhibit 5-HT clearance. However, our second major finding was that genetic inactivation of the 5-HTT in a knock-out mouse not only failed to prevent ethanol-induced inhibition of 5-HT clearance, but actually potentiated this effect. Ethanol-induced inhibition of 5-HT clearance was also potentiated in nonmutant mice by cotreatment with a 5-HTT antagonist. Providing a link with potential behavioral manifestations of this neural phenotype, 5-HTT knock-out mice also exhibited exaggerated sensitivity to behavioral intoxication, as assayed by the sedative/hypnotic effects of ethanol. This clearly demonstrates that the 5-HTT is not necessary for the neural and behavioral effects of ethanol observed herein and that genetic or pharmacological inactivation of the 5-HTT unmasks involvement of other principle mechanisms. These data are intriguing given growing evidence implicating the 5-HTT in the pathophysiology and treatment of alcoholism and neuropsychiatric conditions frequently comorbid with alcoholism, such as depression. The present findings provide new insights into the actions of ethanol on brain function and behavior.